2017
DOI: 10.1097/md.0000000000006518
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic oral cyclosphosphamide as third-line systemic treatment or beyond in patients with inoperable locoregionally advanced recurrent or metastatic nasopharyngeal carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Three studies reported median PFS [21][22][23]. The matched pair analysis [24] showed a bene t for cetuximab-based chemotherapy in terms of superior median PFS and OS.…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies reported median PFS [21][22][23]. The matched pair analysis [24] showed a bene t for cetuximab-based chemotherapy in terms of superior median PFS and OS.…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%
“…Then 67 records including 9 comments or abstracts related to the aim of study were excluded. Finally, 13 records meeting criteria, including 3 randomized control trails [17][18][19], 1 cohort study [20], 4 prospective studied (3 single arm trials [21][22][23], 1 match pair analysis [24]) and 5 retrospective studies [25][26][27][28][29] were included.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the evidence of chemotherapy as subsequent systemic therapy following failure to 1 st line chemotherapy is less well-defined. Single agent without platinum, e.g., gemcitabine, taxane, capecitabine and metronomic cyclophosphamide, is an also acceptable option for heavily pretreated patients (8)(9)(10)(11). Targeted therapy including anti-EGFR (gefitinib and cetuximab), anti-VEGF/VEGFR (axitinib), multi-kinase tyrosine kinase inhibitor (sorafenib and sunitinib) and Akt inhibitor were also evaluated in numerous phase II trials (12)(13)(14)(15).…”
mentioning
confidence: 99%